'It's a challenge': Post primary physical education teachers' experiences of and perspectives on inclusive practice with students with disabilities - McGrath, Ona; Crawford, Susan; O'Sullivan, Dan (European Journal of Adapted Physical Activity, 2019)
Internationally, several studies have indicated insufficient emphasis on the theory and practice of inclusion in relation to disability, in both initial teacher education and continuing professional development programmes for Physical Education (PE) teachers.  This has resulted in some negative attitudes and perceived lack of competency among teachers in relation to inclusive practices in PE. There is a lack of in-depth studies in this regard from an Irish perspective. This current study sought to explore seven PE teachers' experiences and perspectives in relation to the inclusion of students with disabilities in four post primary schools using a multiple case study design. Qualitative data was generated from in-depth semi structured interviews. Teachers felt that there was a lack of both theory and particularly 'hands-on' praxis in initial teacher education and continuing professional education in relation to inclusion and PE. Teachers appear to be comfortable with inclusion; however, the word "challenge" emerged as a concern in relation to interviewees' experiences. This study has implications for more appropriate theoretical and experiential learning in both initial teacher education and continuing professional development for PE teachers to facilitate quality inclusion for students with disabilities
Keywords: inclusion; disability; initial teacher education; continuing professional development; qualitative approach